Assessment of Atrazine Migration in Soil and Groundwater Using Nitrate as an Indicator in an Intensively Cultivated Sugarcane Field, Suphan Buri Province, Thailand - Ratchawang, Sorranat; Chotpantarat, Srilert; Charoenrojying, Pimchaya (Frontiers in Earth Science, 2022)
Groundwater has been widely used in Thailand for many purposes including agricultural activities; therefore, groundwater can be contaminated and affect environment and human health. One of the most applied and imported pesticides is atrazine, which is an herbicide used to control annual broadleaf and grass weeds in sugarcane. Monitoring and reducing the atrazine leaching potential to groundwater would play an important role in preventing this problem. The aim of this study is to evaluate leaching potential of atrazine in Song Phi Nong district, Suphan Buri province via the Attenuation/Retardation Factor model (AF/RF model) and the groundwater ubiquity score (GUS). It was found that most of the agricultural area, especially the sugarcane field, had high leaching potential due to the low adsorption and water holding capacity of the soil. The performance of the model was then evaluated by the result of nitrate (NO3-) detection in groundwater, which has been reported to be pesticide and herbicide leaching indicator. Interestingly, the area with high leaching potential was partly contaminated by high NO3− concentration. However, some factors relating to leaching potential in the area were not considered in the model causing low nitrate concentration detection. The isotopic ratio was also measured in this study to identify sources of NO3−; most of the nitrate in the groundwater samples, as a result, was polluted from human activities, especially from domestic wastewater. The AF/RF model can be risk management, groundwater resource planning assistant leading to human health and environment protection related to pesticide contaminated groundwater.